Indole Alkaloids from Vinca major and V. minor Growing in Turkey - BAHADORİ, FATEMEH; Bahadori, FATEMEH; TOPÇU, GÜLAÇTI; Topcu, Gulacti; KARTAL, MURAT; Boga, Mehmet; Turkekul, Ayla; Kolak, Ufuk; Kartal, MURAT (My University, 2012)
A new indole alkaloid, 11-hydroxypolyneuridine, was isolated from Vinca major subsp. major L. and the known indole alkaloids vallesiachotamine and isovallesiachotamine from Vinca minor L. This is the first report on the alkaloids of both Vinca species growing in Turkey; vallesiachotamine and isovallesiachotamine were isolated from a Vinca species for the first time. V. minor may be considered as a new source for these two alkaloids due to their occurrence in high amount in the aerial parts of the plant. The alkaloid extracts of the two Vinca species were found to have high lipid peroxidation inhibitory and DPPH radical scavenging activities. Anticholinesterase activity of the extracts was also very strong.